ПРИЗНАЧЕННЯ, ЗВІЛЬНЕННЯ ЧЛЕНІВ РАХУНКОВОЇ ПАЛАТИ УКРАЇНИ ТА ГАРАНТІЇ ЇХ ПРАВОВОГО СТАТУСУ ЗА НОВИМ ЗАКОНОМ УКРАЇНИ «ПРО РАХУНКОВУ ПАЛАТУ» - Савченко, Леся Анатоліївна (SUPREMANCE OF LAW, 2016)
This article analyzes the provisions of the Law of Ukraine “On the Accounting Chamber” 2015 and other regulations which concerning the appointment, dismissal the members of the Accounting Chamber and guarantees of their legal status, the author expresses the opinion of concerning amending and supplementing.